1993
DOI: 10.1159/000468690
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Ubiquitination of the 26S Proteasome Complex

Abstract: This article reviews recent studies from our laboratory on protein regulators of the proteasome (multicatalytic proteasome complex) in red blood cells. A 240-kD inhibitory component (CF-2) exists in 26S proteasome complexes in a form which is conjugated to ubiquitin. Interestingly, this factor was shown to be identical to 8-aminolevulinic acid dehydratase (ALAD), involved in heme synthesis. A distinct 200-kD inhibitor of the proteasome is not present in the 26S complex. A 32-kD subunit of the 20S proteasome ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Additionally, proteins were found that have roles in protein trafficking/localization, protein structure, and the immune system, consistent with previously reported roles for ubiquitination1114. Many ubiquitin-conjugating enzymes, ubiquitin ligases, and 26S proteasome regulatory subunits are ubiquitinated, consistent with previous studies that many proteins involved in proteasome degradation pathways are ubiquitinated15, 16. Some proteins found to be ubiquitinated extend findings regarding the role of ubiquitination in certain cellular processes.…”
supporting
confidence: 89%
“…Additionally, proteins were found that have roles in protein trafficking/localization, protein structure, and the immune system, consistent with previously reported roles for ubiquitination1114. Many ubiquitin-conjugating enzymes, ubiquitin ligases, and 26S proteasome regulatory subunits are ubiquitinated, consistent with previous studies that many proteins involved in proteasome degradation pathways are ubiquitinated15, 16. Some proteins found to be ubiquitinated extend findings regarding the role of ubiquitination in certain cellular processes.…”
supporting
confidence: 89%
“…The biological function of the 11 S regulator is not fully understood but it is presumed to be related to the proteasomal role in antigen processing. 20 Other speculations involve the 11 S regulator as an adapter molecule between the 20 S proteasome and chaperons, an idea that would be consistent with the report that some proteasome preparations contain chaperons. 21 When the other complex, the 19 S regulator, binds to both ends of the 20 S proteasome, a new protease is formed: the 26 S proteasome.…”
Section: The Proteasome: Function Regulation and Distributionsupporting
confidence: 54%
“…The 11 S regulator is a heptameric or hexameric structure that binds to the outer ring of the 20 S proteasome and modulates its activity. The biological function of the 11 S regulator is not fully understood but it is presumed to be related to the proteasomal role in antigen processing 20 . Other speculations involve the 11 S regulator as an adapter molecule between the 20 S proteasome and chaperons, an idea that would be consistent with the report that some proteasome preparations contain chaperons 21 …”
Section: The Proteasome: Function Regulation and Distributionmentioning
confidence: 65%
“…Several subunits of the proteasome have been reported to be phosphorylated in vivo [43, 44], however, relatively few studies have addressed how phosphorylation may regulate proteasome function. Phosphorylation might regulate proteasome subunit assembly, disassembly, or distinct proteasome activities, such as peptidase activity, ATPase activity, ubiquitin binding, and/or deubiquitinating activities.…”
Section: Resultsmentioning
confidence: 99%